1999
DOI: 10.1242/jeb.202.3.315
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for branchial acid excretion in marine fish: identification of multiple Na+/H+ antiporter (NHE) isoforms in gills of two seawater teleosts

Abstract: Both Na+/H+ exchange and the electrogenic extrusion of H+ via an H+-ATPase have been postulated to drive acid excretion across the branchial epithelium of fishes. While the H+-ATPase/Na+ channel system appears to be the predominant mechanism in some freshwater species, it may play a reduced role in seawater and brackish-water animals, where high external Na+ concentrations may thermodynamically favor Na+/H+ exchange driven by a Na+/H+ antiporter (NHE). In this study, we used molecular and immunological methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…OA alone or coupled with ocean warming poses globalscale threats to marine life ranging from the invisible scale of microbes to ecosystem levels [6][7][8][9]. Given their efficient capacity for maintaining acid-base homeostasis, fishes have long been considered to be robust organisms capable of tolerating OA [10][11][12][13]. However, reported indirect impacts of OA include both inter-and intraspecific changes in sensory behaviours [14], which result from directly altered neurosensory systems [15][16][17][18][19][20][21][22][23] that ultimately affect reproduction, fitness and mortality [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…OA alone or coupled with ocean warming poses globalscale threats to marine life ranging from the invisible scale of microbes to ecosystem levels [6][7][8][9]. Given their efficient capacity for maintaining acid-base homeostasis, fishes have long been considered to be robust organisms capable of tolerating OA [10][11][12][13]. However, reported indirect impacts of OA include both inter-and intraspecific changes in sensory behaviours [14], which result from directly altered neurosensory systems [15][16][17][18][19][20][21][22][23] that ultimately affect reproduction, fitness and mortality [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on rainbow trout have corroborated this hypothesis by demonstrating that gill V-H + -ATPase activity, immunoreactivity and mRNA expression all increase after exposure to environmental hypercapnia (Lin and Randall, 1993;Lin et al, 1994;Sullivan et al, 1995;Sullivan et al, 1996;Perry et al, 2000). Studies on branchial V-H + -ATPase in a true marine teleost have yet to be published, but the transporter's role in acid-base regulation of seawater teleosts is assumed to be minimal, given the favorable Na + gradient for Na + /H + exchangers (see Claiborne, 1998;Claiborne et al, 1999).…”
Section: Introductionmentioning
confidence: 93%
“…It is generally accepted that sodium (Na + ) and hydrogen (H + ) exchangers (NHEs) are the major transporters of acid (H + ) secretion by ionocytes ( Hwang and Chou, 2013 ; Liu et al, 2013 ). Several NHE isoforms (NHE1, NHE2, NHE3, NHE5, NHE6, NHE7, and NHE8) were found in fishes, ( Hu et al, 2013 ; Yan and Hwang, 2019 ); and NHE1, NHE2, and NHE3 were found in the gills of fishes ( Claiborne et al, 1999 , 2002 ; Edwards et al, 2005 ). In freshwater (FW) fishes, NHE3 at the apical membrane was demonstrated to be the major isoform for acid secretion by ionocytes ( Yan et al, 2007 ; Inokuchi et al, 2008 ; Wu et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to NHE3, however, the localization and function of NHE2 in ionocytes of SW fish are still uncertain. Several studies showed that messenger (m)RNA and protein expressions of NHE2 were stimulated by acidic water or infusion of HCl, suggesting that NHE2 is involved in acid secretion by gills ( Claiborne et al, 1999 ; Tresguerres et al, 2005 ; Catches et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%